2020
DOI: 10.1111/ggi.14095
|View full text |Cite
|
Sign up to set email alerts
|

Management guideline for Werner syndrome 2020 1. Dyslipidemia and fatty liver associated with Werner syndrome

Abstract: For the purpose of examining the characteristics of dyslipidemia and fatty liver in patients with Werner syndrome in Japan in recent years, we searched all case reports of Japanese Werner syndrome reported on Medical Online and PubMed since 1996, and collected and examined the data and clinical features described in these reports. In addition, as there are few descriptions of treatment methods in these reports from Medical Online and PubMed, we analyzed 12 cases for which detailed data on treatment methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…4 According to a systematic review of Japanese WS patients by Tsukamoto et al, fatty liver was found in 12 of 44 patients with WS, many of whom were not obese, but reported an association with high triglyceride and low high-density lipoprotein cholesterol levels. 5 Similarly, the present case was not accompanied by obesity, and no increase in blood low-density lipoprotein cholesterol was observed, but a moderate increase in triglyceride (200 mg/dL) and low high density lipoprotein cholesterol levels (30 mg/dL) were observed.…”
Section: Dear Editorsupporting
confidence: 68%
See 1 more Smart Citation
“…4 According to a systematic review of Japanese WS patients by Tsukamoto et al, fatty liver was found in 12 of 44 patients with WS, many of whom were not obese, but reported an association with high triglyceride and low high-density lipoprotein cholesterol levels. 5 Similarly, the present case was not accompanied by obesity, and no increase in blood low-density lipoprotein cholesterol was observed, but a moderate increase in triglyceride (200 mg/dL) and low high density lipoprotein cholesterol levels (30 mg/dL) were observed.…”
Section: Dear Editorsupporting
confidence: 68%
“…Although primary central nervous system lymphoma is a rare neoplasm of the brain, patients with HIV infection have a 1000-fold increased risk of developing cerebral lymphoma. 5 The present case highlights the fact that we should be aware that a wandering older person might have a treatable disease, such as HIV-associated primary central nervous system lymphoma in this case. In addition, an older person can suddenly develop AIDS without a prior diagnosis of HIV infection.…”
Section: Hiv-associated Cerebral Lymphoma In An Elderly Patientmentioning
confidence: 65%
“…Disease prevalence 1 in 20 million 5) 9.0 in 1 million in Japan 87) , 1.0 to 2.7 in 1 million globally 47) Ethnicity Ubiquitous 7) Relatively prevalent in Japanese and Sardinian 47) Sex Equally affected 7) Equally affected 48) Lifespan Average 14.5 years 5) Average 55.0 years 65) , median 54.3 years 88) Responsible gene and frequent mutation LMNA: c.1824C T (90% of patients) 5) WRN: c.3139-1G C (70.7% of allele in Japanese patients), WRN: c.1105C T (18.6% of allele in non-Japanese patients) 47) Diabetes or IGT 15.4% of patients 6) 67.5% of patients 67) Dyslipidemia 71.4% of patients 6) 65.0 to 85.0% of patients 52,67) Hypertension 46.7% of patients 6) 42.5% of patients 67) CVD 100% had adventitial thickening in the carotid artery, 18.2% had the low anklebrachial index 6) 15% had ASO, 2.5% had AP or MI, none had cerebral artery disease 67) Causes of death (percentage of total) Heart failure (80%), head injury (9%), complications of surgery (4%), stroke (3%) 7) Malignancy (56%), AMI (28%), infection (14%), cerebral bleeding (2%) 65) Abbreviations: IGT, impaired glucose tolerance; ASO, atherosclerosis obliterans; AP, angina pectoris; MI, myocardial infarction; AMI, acute myocardial infarction.…”
Section: Hgps Wsmentioning
confidence: 99%
“…If multiple corn/callus and calcification of the Achilles tendon are observed, genetic testing should be conducted to confirm the diagnosis. Please refer to the "Management guideline for Werner syndrome 2020" series for the main strategy to treat each specific symptom [52][53][54][55][56][57][58][59] .…”
Section: Clinical Characteristics Of Wsmentioning
confidence: 99%
See 1 more Smart Citation